Low-dose irradiation of the gut improves the efficacy of PD-L1 blockade in metastatic cancer patients - Chen, Jianzhou; Levy, Antonin; Tian, Ai-Ling; Huang, Xuehan; Cai, Guoxin; Fidelle, Marine; Rauber, Conrad; Ly, Pierre; Pizzato, Eugénie; Sitterle, Lisa; Piccinno, Gianmarco; Liu, Peng; et al. (Cancer cell, 2025)
The mechanisms governing the abscopal effects of local radiotherapy in cancer patients remain an open conundrum. Here, we show that off-target intestinal low-dose irradiation (ILDR) increases the clinical benefits of immune checkpoint inhibitors or chemotherapy in eight retrospective cohorts of cancer patients and in tumor-bearing mice. The abscopal effects of ILDR depend on dosimetry (≥1 and ≤3 Gy) and on the metabolic and immune host-microbiota interaction at baseline allowing CD8+ T cell activation without exhaustion. Various strains of Christensenella minuta selectively boost the anti-cancer efficacy of ILDR and PD-L1 blockade, allowing emigration of intestinal PD-L1-expressing dendritic cells to tumor-draining lymph nodes. An interventional phase 2 study provides the proof-of-concept that ILDR can circumvent resistance to first- or second-line immunotherapy in cancer patients. Prospective clinical trials are warranted to define optimal dosimetry and indications for ILDR to maximize its therapeutic potential.
Keywords: Gastrointestinal Microbiome; Humans; lidé středního věku; střeva; Intestines; Female; Aged; inhibitory kontrolních bodů; senioři; lidé; Immunotherapy; zvířata; myši; myši inbrední C57BL; B7-H1 Antigen; CD8-Positive T-Lymphocytes; Mice; CD8-pozitivní T-lymfocyty; Neoplasm Metastasis; metastázy nádorů; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Immune Checkpoint Inhibitors; Neoplasms; Mice, Inbred C57BL; nádory; retrospektivní studie; střevní mikroflóra; Animals; antigeny CD274; mužské pohlaví; imunoterapie